Cold War Canada: The Making of a National Insecurity State, 1945-1957 - Avery, Donald Howard (Labour / Le Travail, 1997)
The article reviews the book, "Cold War Canada: The Making of a National Insecurity State, 1945-1957," by Reg Whitaker and Gary Marcuse.
Keywords: 1945-; BOOKS – Reviews; COLD War Canada: The Making of a National Insecurity State 1945-1957 (Book); Canada; History; MARCUSE; Gary; Nonfiction; WHITAKER; Reg